Flow diverter therapy for mirror-like aneurysms at the middle cerebral artery trifurcation: a case report - Zheng, Lin; Yu, Jinlu (Frontiers in Surgery, 2026)
Flow diverters (FDs) can be deployed to treat certain intracranial aneurysms by covering the parent artery origin without direct neck coverage, though this approach remains uncommon. This present case demonstrated successful treatment of mirror-like aneurysms at the middle cerebral artery (MCA) trifurcation using this technique. A 57-year-old male patient presented with subarachnoid hemorrhage. Computed tomography angiography revealed mirror-like aneurysms of the left MCA. Physical examination showed a Hunt-Hess scale score of Grade II. Endovascular treatment was performed. Under general anesthesia, digital subtraction angiography (DSA) demonstrated left MCA trunk division into triple branches. The superior and inferior branches displayed mirror-like dissecting aneurysms, while the middle branch appeared normal. Following coiling of both aneurysms, a FD was deployed in the middle branch to cover the origins of the superior and inferior branches. Postoperatively, the patient developed motor aphasia due to vasospasm. The continuous nimodipine infusion treatment resulted in the relief of the symptom. At six-month follow-up, the patient had mild motor aphasia. DSA confirmed occlusion of both the superior and inferior branches with the aneurysms, while preserving the middle branch to supply the left MCA territory. This case demonstrates that for mirror-like MCA aneurysms located at the superior and inferior branches of a MCA trifurcation, deploying a FD in the normal middle branch to cover the origins of the two aneurysmal branches may result in occlusion of the parent arteries harboring the aneurysms. However, this novel approach warrants cautious application as it remains non-routine.